Effect of protein structure changes during different power ultrasound thawing on emulsification properties of common carp (Cyprinus carpio) myofibrillar protein - Qinxiu Sun; Baohua Kong; Ouyang Zheng; Shucheng Liu; Xiuping Dong (Ultrasonics Sonochemistry, 2023)
The impact of ultrasound thawing (UT) at different power (0 W, 100 W/0.132 W·cm−2, 300 W/1.077 W·cm−2, and 500 W/1.997 W·cm−2, namely WT, UT-100, UT-300, and UT-500) on protein structure, aggregation, and emulsifying properties of common carp (Cyprinus carpio) myofibrillar protein were investigated in the present study. The result showed that the reactive sulfhydryl content, total sulfhydryl content, protein solubility, and absolute potential of UT-300 samples were obviously higher than those of other thawed samples, while the turbidity of UT-300 samples was lower (P < 0.05), which indicated that proper UT power was beneficial to inhibit protein aggregation caused by thawing, while too low (100 W) or too high (500 W) ultrasonic power had poor effect. The Ca2+-ATPase activity and thermal stability of UT-300 samples were much higher than those of other thawed samples (P < 0.05), indicating that UT-300 inhibited myosin denaturation and thermal stability reduction of thawed products. The α-helix content of UT-300 samples was higher than that of other thawed samples, while the β-sheet content was significantly lower than that of other thawed samples (P < 0.05). The fluorescence intensity of UT-300 samples was higher than that of other thawed samples, and the λmax of UT-300 samples and UT-100 samples were lower than that of other thawed samples, which indicated that UT-300 could effectively inhibit the alteration of protein secondary structure and tertiary structure during thawing. The emulsifying activity of UT-300 samples was significantly higher than that of WT samples, and the droplet diameter of UT-300 samples was also lower than that of WT samples (P < 0.05), which indicated that UT-300 inhibited the decrease of emulsifying property during thawing. Overall, moderate ultrasonic power (300 W) could effectively inhibit the protein aggregation and structural changes during thawing, led to the decrease of emulsifying activity.